2011
DOI: 10.1371/journal.pone.0022686
|View full text |Cite
|
Sign up to set email alerts
|

Heaven It's My Wife! Male Canaries Conceal Extra-Pair Courtships but Increase Aggressions When Their Mate Watches

Abstract: Many animals live in a communication network, an environment where individuals can obtain information about competitors or potential mates by observing interactions between conspecifics. In such an environment, interactants might benefit by changing their signalling behaviour in the presence of an audience. This audience effect seems widespread among species, has been observed during various types of interaction (e.g. intra-sexual vs. inter-sexual interaction) and varies according to the social context (e.g. g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…As juncos are socially monogamous and regularly engage in extra-pair behavior (Gerlach et al, 2011), it seems unlikely that males would respond aggressively to a potential extra-pair mate during the breeding season. One context in which a male might be expected to exhibit aggressive behavior towards a female conspecific is in the presence of his social mate (e.g., Ung et al, 2011). Contrary to this prediction, males produced slow SRS towards a female conspecific in both the presence and absence of their social mate in each of our experiments.…”
Section: Srs and Aggressive Signalingcontrasting
confidence: 69%
“…As juncos are socially monogamous and regularly engage in extra-pair behavior (Gerlach et al, 2011), it seems unlikely that males would respond aggressively to a potential extra-pair mate during the breeding season. One context in which a male might be expected to exhibit aggressive behavior towards a female conspecific is in the presence of his social mate (e.g., Ung et al, 2011). Contrary to this prediction, males produced slow SRS towards a female conspecific in both the presence and absence of their social mate in each of our experiments.…”
Section: Srs and Aggressive Signalingcontrasting
confidence: 69%
“…The audience effect is a wide-spread phenomenon and has been studied in various contexts (e.g., feeding [ 77 ], food caching [ 78 ], predator detection [ 79 ], and mate choice [ 80 ]). The audience effect has been studied in various taxa (insects [ 81 , 82 ], birds [ 83 , 84 , 85 , 86 , 87 , 88 ], mammals [ 78 , 79 , 89 , 90 , 91 , 92 ]), especially in fish: e.g., in the fighting fish Betta splendens [ 93 , 94 , 95 ], in the three-spine stickleback G. aculeatus [ 96 ], in the guppy P. reticulata [ 64 , 80 ], in the sailfin molly P. latipinna [ 97 , 98 ], and in the Atlantic molly P. mexicana [ 99 , 100 , 101 ].…”
Section: Introductionmentioning
confidence: 99%
“…The audience is not taking part in the interaction, but its presence is recognized by the interacting individuals. This audience effect has been intensively investigated in Siamese fighting fish ( Betta splendens ) (e.g., [ 20 , 21 , 22 ]) and the livebearing Poeciliidae (e.g., [ 7 , 23 , 24 , 25 ]), and evidence for audience effects has also been found in insects (e.g., [ 26 , 27 ]), mammals (e.g., [ 28 , 29 , 30 ]) and birds (e.g., [ 31 , 32 , 33 , 34 , 35 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Baltz and Clark [ 32 ] found that male budgerigars ( Melopsittacus undulates ) limited their extra-pair courtship to times when their mates could not overserve them. Likewise, male canaries ( Serinus canaria ) reduced their extra-pair courtship in the presence of their partner [ 33 ]. Hoi and Griggio [ 35 ] found that male and female bearded reedlings ( Panurus biarmicus ) adjust their pair-bond investment mainly in response to the presence or absence of a competitor.…”
Section: Introductionmentioning
confidence: 99%